2018
DOI: 10.1021/acs.estlett.8b00237
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Quantitative PCR Measurements of Fecal Indicator Bacteria and Human-Associated Source Tracking Markers in a Texas River following Hurricane Harvey

Abstract: Hurricane Harvey has caused unprecedented devastation to huge parts of southeastern Texas, particularly damaging the wastewater infrastructure resulting in release of sewage contamination into environmental waters. The purpose of this study was to conduct a preliminary assessment of fecal indicator bacteria (Escherichia coli and enterococci) and human-associated fecal genetic markers (human-associated Bacteroidales), measured using qPCR assays, across a Texas river impacted by Hurricane Harvey. Water samples w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 31 publications
3
29
1
Order By: Relevance
“…Another study done in Houston after Hurricane Harvey sampled water from areas that had been affected by the floods. There, through qPCR, they found average concentrations of 2.1 log10 copies/100mL of E. coli and 5.7 log10 copies/100 mL of Enterococci [33]. Both studies found higher concentrations than our maximum E. coli and Enterococci concentrations of 1.9 log10 gene copies/100 mL and 2.1 log10 gene copies/100 mL.…”
Section: Discussioncontrasting
confidence: 43%
“…Another study done in Houston after Hurricane Harvey sampled water from areas that had been affected by the floods. There, through qPCR, they found average concentrations of 2.1 log10 copies/100mL of E. coli and 5.7 log10 copies/100 mL of Enterococci [33]. Both studies found higher concentrations than our maximum E. coli and Enterococci concentrations of 1.9 log10 gene copies/100 mL and 2.1 log10 gene copies/100 mL.…”
Section: Discussioncontrasting
confidence: 43%
“…A recent mapping-based study in Ho Chi Minh City, Vietnam, estimated that 83% of urban informal settlement areas were exposed to floods (for a 1000-year return period) compared to 68% of the city as a whole 65 , not considering the impacts of flood protections such as drainage systems that are unlikely to be equitably distributed between urban informal settlements and wealthier neighborhoods 63 . Floodwaters have been demonstrated to contain elevated levels of antimicrobial resistance genes (e.g., sul1) and elevated levels of several fecal pathogen markers, including of Aeromonas spp., E. coli, Enterococcus, Klebsiella pneumoniae, and Clostridium perfringens [67][68][69] . In Vellore, India, children living in parts of urban informal settlements that were susceptible to flooding were recently shown to have increased odds of enteric infection during rainfall events 70 .…”
Section: Insufficient Drinking Water Drainage and Sanitation Infrastmentioning
confidence: 99%
“…Aging sewer infrastructure in the USA and elsewhere will require rapid methods to assess fecal contamination of water [ 1 , 2 •, 3 ]. The number of extreme weather events including flooding events is forecast to increase with climate change and has been associated with contamination of water resources [ 4 6 ]. Also, the increasing threat of antimicrobial resistance is making it all the more important to lower the rates of infections across the globe, especially infections that require antibiotic treatment, and to identify environments contaminated with antibiotic-resistant pathogens [ 7 – 9 ].…”
Section: Introductionmentioning
confidence: 99%